Developmental Ultrasound Characteristics in Guinea Pigs: Similarities with Human Pregnancy - Garcia-Herrera, C; Navarrete-Rosales, A (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Background: Biometrical and blood flow examinations are fundamental for assessing fetoplacental development during pregnancy. Guinea pigs have been proposed as a good model to study fetal development and related gestational complications; however, longitudinal growth and blood flow changes in utero have not been properly described. This study aimed to describe fetal and placental growth and blood flow of the main intrauterine vascular beds across normal guinea pig pregnancy and to discuss the relevance of this data for human pregnancy. Methods: Pregnant guinea pigs were studied from day 25 of pregnancy until term (day ~70) by ultrasound and Doppler assessment. The results were compared to human data from the literature. Results: Measurements of biparietal diameter (BPD), cranial circumference (CC), abdominal circumference, and placental biometry, as well as pulsatility index determination of umbilical artery, middle cerebral artery (MCA), and cerebroplacental ratio (CPR), were feasible to determine across pregnancy, and they could be adjusted to linear or nonlinear functions. In addition, several of these parameters showed a high correlation coefficient and could be used to assess gestational age in guinea pigs. We further compared these data to ultrasound variables from human pregnancy with high similarities. Conclusions: BPD and CC are the most reliable measurements to assess fetal growth in guinea pigs. Furthermore, this is the first report in which the MCA pulsatility index and CPR are described across guinea pig gestation. The guinea pig is a valuable model to assess fetal growth and blood flow distribution, variables that are comparable with human pregnancy. © 2023 by the authors.